2021
DOI: 10.1002/jdn.10118
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders during pregnancy and postpartum depression: A systematic review and meta‐analysis

Abstract: Background Postpartum depression (PPD) is one of the most important mental disorders in recent years. However, the effects of prenatal sleep disorders on the development of PPD among pregnant women have not been elucidated. This review aims to provide a summary of the literature evaluating the relation between sleep disorders during pregnancy and PPD. Method A systematic literature search was conducted in PubMed, Web of Science, Scopus, Google Scholar, and Embase up to September 2020. All observational studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 37 publications
1
14
1
Order By: Relevance
“…Results of the present study were not in line with findings suggesting that poor sleep in pregnancy is associated with post-partum depression ( 33 ). This may be explained by the fact that studies on post-partum depression have carried out their sleep assessments in late pregnancy or post-partum, whereas women participating in the present study recorded their sleep patterns during the first half of pregnancy.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Results of the present study were not in line with findings suggesting that poor sleep in pregnancy is associated with post-partum depression ( 33 ). This may be explained by the fact that studies on post-partum depression have carried out their sleep assessments in late pregnancy or post-partum, whereas women participating in the present study recorded their sleep patterns during the first half of pregnancy.…”
Section: Discussioncontrasting
confidence: 99%
“…Based on objective measurements, the findings of this study confirm prior findings of women's subjective reporting of sleep disturbances and their risk of developing depressive symptoms during pregnancy ( 30 , 31 , 33 ). Thus, this study has added important value to the subjective reports of women by establishing that poor sleep, in this case objectively evaluated by actigraphy, may contribute to an increased risk of depression during pregnancy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We do not know if the 14 women who left the study before follow‐up may have developed a depression, but as shown in Dataset S1, they suffered more from sleep disturbances in pregnancy, which is a known risk factor for depression. 22 , 80 Further, we have no information on the longitudinal changes in 5‐HIAA and EPDS, for ethical and practical reasons. However, by studying these phenomena in healthy women, we may have unmasked associations that would have been obscured by other risk factors for PND.…”
Section: Discussionmentioning
confidence: 99%
“…Significant sleep disturbance is not only common, but also adverse for health 9 , 10 . Multitudinous studies have researched the relationship between sleep during pregnancy and subsequent maternal and fetal outcomes 11 , 12 . However, some previous studies reported that sleep had no association with adverse pregnancy outcomes, whereas other emerging evidence suggested that sleep was involved in adverse maternal complications and fetal outcomes.…”
Section: Introductionmentioning
confidence: 99%